Penetrating Micelle for Reversing Immunosuppression and Drug Resistance in Pancreatic Cancer Treatment (Small 18/2022). Issue 18 (5th May 2022) - Chen, Qinjun; Wang, Qingbing; Wang, Yu; Chu, Yongchao; Luo, Yifan; You, Haoyu; Su, Boyu; Li, Chao; Guo, Qin; Sun, Tao; Jiang, Chen
Abstract : Pancreatic Cancer Treatment In article number 2107712, Tao Sun, Chen Jiang, and co‐workers develop a versatile drug delivery system that can co‐encapsulate two hypoxia‐responsive prodrugs modified from gemcitabine and a STAT3 inhibitor. The system can respond to the gradient pH variation in the tumor microenvironment to realize higher penetration by reversing its surficial charges, with the aim of simultaneously reversing immunosuppression and drug resistance in pancreatic cancer treatment.